The Role of Kaizen's Strategy (Japanese Model) in Empowering Human Resources (Field study on female employees in the general administration of education in Jeddah) - Felmban, Ahood Tariq Mohammed; Alsharief, Raja Yahya Ahmed (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to recognize the role of Kaizen strategy (Japanese Model) in the empowerment of human resources; a field study on female employees in the general administration of education in Jeddah. The descriptive and analytical method was used. The study population reached (494) female employee, where a simple random sample was taken. The researcher, in order to achieve the objectives of the study, designed a questionnaire containing (30) paragraphs as a tool for collecting data, which was distributed to (276) female employees. The number of questionnaires which are valid for analysis reached (234) questionnaire. The data were statistically processed using the Statistical Package for the Social Sciences (SPSS). The study reached several results, the most important of which is: There is a statistically significant relationship between the Kaizen strategy and the empowerment of human resources at the level (α≤0.05). The results also showed the degree to which the majority of the sample of the female employees of the general administration of education in Jeddah met the basic concepts of the Kaizen strategy, with an approval rate of (71.2%). The degree of empowerment of human resources in the organization was with an approval rate of (59.7%). In addition, the opinion of the female employees was positive for the role that the implementation of the Kaizen strategy will play in empowering human resources in the organization, with approval rate of (82.9%). The most approved word is (Its Implementation will reduce the waste of operations, effort, time, errors and cost). The most important recommendations of the study: the need to spread the philosophy of Kaizen in governmental and private organizations in the Kingdom of Saudi Arabia and adoption the philosophy of Kaizen in the organization as a modern management method helps to achieve services' quality and the development of performance on a continuous basis to obtain positive results, as well as working to empower workers by using modern methods of management, develop their skills to achieve the best levels of work and achievement, provide working environment that increases the positive interaction between employees and raise the level of job performance and quality of services and outputs.
Keywords: kaizen; empowerment; human resources; empowering human resources